Diffusion of innovation: a social network and organizational learning approach to governance of a districtwide leadership team - Yi-Hwa Liou; Alan J. Daly (Sociedad Iberoamericana de Pedagogía Social, 2016)
District and school leaders play particularly important roles in leading districtwide improvement, as they are increasingly held accountable for bringing about change and improvement for educational innovation and excellence.  While conventional districtwide governance places much of its focus on technical and administrative matters such as policy development, supervision, and monitoring progress. This technical focus often overlooks the fundamental aspect that drives the progress of improvement-the social infrastructure shaped by interpersonal relationship. Responding to recent scholarships that calls for a networked approach to governance, this study examined the change effort of a districtwide leadership team over three points in time drawing on social network theory and analysis focused on district governance.  Specifically, we focused on the type of interpersonal relationship in which leaders engaged with each other in sharing and exchanging innovative ideas as these efforts may support better governance. Additionally, we explored organizational learning as a way to examine climate in support of districtwide innovative efforts during change process. Our findings from leaders indicated increased innovative behaviors and perceived climate on organizational learning over time. The findings suggested that leaders increased connections around risk taking, regardless of their work level over time. This increased connectedness around innovation was coupled with an increase in leaders' perception of the district's learning climate, suggesting a cohesive approach to governance and improvement.